Comparative study of entropy distribution for generalized fluid between an inclined channel in the perspective of classical and non-Fourier’s law - Nidhal Ben Kheder; Sohail Rehman; Sultan Alqahtani; Hashim; Sultan Alshehery (Engineering Science and Technology, an International Journal, 2023)
The key challenge in the design of thermal appliances is to degrade entropy production with maximal energy dissipation to improve system efficiency in a variety of engineering applications, such as nozzle design, converging die, and rocket design. Due to the existence of both tangential and radial components, which have a significant impact on the fluid movement, coupled transport rates, and entropy development in an inclined channel presents a greater challenge. The current inquiry intended to address the combined impacts of Cattaneo-Christove (C-C) heat flux and classical theory on thermal dissipation, along with irreversibility distribution in a tilted porous media. The Carreau nanofluid confined between two finite intersecting plates in the presence of a porous Darcy-Forchheimer medium is examined. The C-C heat flux, variable thermal conductivity, and mass diffusivity are all used to investigate heat transport. The flow originates from a source located at the intersection of the plates and constitutes the momentum conservation. The investigation includes entropy and Bejan analysis. The premises guide the mathematical modelling of the flow field. Through bvp4c techniques, numerical solutions are attained. Converging section velocity increases in response to increased porosity and the Forchheimer number. Variation in temperature is significant when classical heat flux is reverted. Higher thermophoretic and porosity parameters result in a higher rate of entropy formation, while the Darcy parameter promotes drastic increase. Bejan is an escalating function of Brownian and Darcy parameters, while the porosity parameter causes it to fall. Porosity and the Forchheimer number regulate skin friction.